ANALYSIS OF STUDENT RESPONSE TO KWLA (WHAT I ALREADY KNOW, WHAT I WANT TO KNOW, WHAT I LEARNED, AND THE AFFECT OF THE STORY) STRATEGY IN THE LEARNING READING COMPREHENSION - Yulianah Prihatin; Raras Hafiidha Sari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine students' responses to learning to read narrative text comprehension using the KWLA strategy (What I Already Know, What I Want to Know, What I Learned, and The Affect of the Story). A collecting data in this study used a questionnaire in the form Unstructured questionnaires and interviews The results of the data were obtained and analyzed quantitatively qualitatively The data generated in the form of numbers were then described Based on the results of the study, it was found that aspects 1 to 5 that contained responses of students' interest in learning thus obtained by 90.4% included in the category very good.In aspects 6 to 10 which contain student responses to ease in understanding and learning the material obtained a percentage of 89.1% included in the very good category.In aspects 11 to 13 which contain student responses in the activity and courage to express opinions in the learning process a percentage of 87 is obtained , 9% in the category of very good, and aspects 14 to 15 which contain responses to the ease of students in concluding learning activities get an average percentage of 90.2% included in the very good category. This shows that the KWLA strategy is able to increase student interest in efforts to improve reading comprehension skills.